Training and mentoring on preparing microscopic permanent and temporary slides for junior high school science teachers using local materials - Wahyuni, Sri; Hindun, Iin; Nurwidodo, N. (Journal of Community Service and Empowerment, 2026)
Practical science learning requires adequate microscope slides to support students’ science process skills. Yet many schools have limited slide collections because commercial preparations are expensive and hard to access. This community service program aimed to (1) improve junior high school science teachers’ knowledge, attitudes, and skills in producing temporary and permanent microscopic slides, (2) promote the use of safe and readily available local materials, and (3) integrate the resulting slides into lesson plans and student worksheets. The program consisted of socialization, hands-on training, workshops, one-month mentoring, and monitoring–evaluation. Participants were four science teachers from SMP Muhammadiyah 2 Batu and SMP Muhammadiyah 8 Batu (Kota Wisata Batu, East Java, Indonesia). Using a 1–4 rubric, pre- and post-tests showed marked improvements in knowledge (mean 1.9 to 3.4), attitudes (mean 1.5 to 3.5), and skills (mean 1.5 to 3.3). Overall, structured practice supported by mentoring strengthened teachers’ independence in producing affordable laboratory media and improved the feasibility of practical-based biology learning.